PATIENT SATISFICATION AS CONSUMERS: A LITERATURE REVIEW ON THE DETERMINANTS OF HEALTH SERVICE QUALITY IN THE JKN ERA - Wulandari, Reny Yulita; Rachmawan, Ade; Hartono, Budi; Daud, Alfani Ghutsa (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Patient satisfaction is a key indicator in assessing the quality of healthcare services, particularly within the National Health Insurance (JKN) system, which aims to provide equitable access to healthcare for all Indonesian citizens. In the context of patients as consumers, understanding the determinants of satisfaction is crucial for improving service quality and maintaining public trust. This study is a literature review that aims to identify and analyze the factors influencing patient satisfaction based on findings from eleven relevant scientific articles. The method used is a literature review with a descriptive-qualitative approach. The review shows that service quality dimensions such as responsiveness, assurance, and empathy consistently have a significant influence on patient satisfaction. Additionally, factors such as perceived service equality between BPJS and non-BPJS patients, institutional image, and prior service experiences also affect satisfaction levels. These findings indicate that patient satisfaction is not only determined by technical aspects of service but also by relational aspects and perceptions of fairness. Therefore, improving service quality oriented towards patients' needs and expectations is essential to support the successful implementation of JKN sustainably.